Результаты огневого испытания железобетонных конструкций на огнестойкость с использованием стержневых волоконно-оптических датчиков деформации - Polevoda Иван; Zaynudinova Наталья (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
Results of fire test of reinforced concrete structure with using fiber-optical sensor of the deformation are presented. The ways of fiber-optical sensors protection at fire test are proposed.